Origin of the Milky Way Disk of Satellites: Collision of Two Disk Galaxies - Bohórquez Pacheco, Omar Alfonso; Casas Miranda, Rigoberto A. (TECCIENCIA, 2016)
The dwarf satellite galaxies of the Milky Way are structures that are distributed around the galaxy in an anisotropic manner on a structure called Disk of Satellites (DoS). This structure does not match the predictions made by the cold dark matter cosmological model, which predicts a fully isotropic distribution around the Milky Way. To explain the spatial distribution of the satellite galaxies several models have been proposed. One of these models raises the possibility that these galaxies and their spatial distribution were generated by the collision of two disk galaxies several billion years ago. This paper shows N-body simulations performed with the Gadget-2 code to determine whether this event occurred in this way. An analysis for different mass ratios between the incident galaxy, called ghost galaxy, and the host galaxy or target galaxy is performed. Finally a cluster analysis on the collision remains is performed to determine the spatial distribution of the satellite galaxies.